A new species of Conopsia Strand, 1913 (Lepidoptera: Sesiidae: Tinthiinae) from West Africa - Sáfián, Szabolcs; Bartsch, Daniel (Zootaxa, 2018)
A new species of Sesiidae, discovered during a Lepidoptera survey in the Nimba Mountains, Guinea (West Africa) is described as Conopsia puehringeri sp. nov. The new species is compared to its potential sister species C. bicolor (Le Cerf, 1917), in sense of external morphology and genitalia structure. Male specimens and genitalia of both studied species are depicted.